Higher Educational Mass Definition of Technical and Tactical Actions in Competitive Activities of Girls Wrestlers - Mo'ydinov Iqboljon Abduxamidovich; Boltaboev Khamidullo Khabibulloevich; Sheraliyeva Sahobat Adhamovna (European Science Publishing, 2023)
The accuracy of female wrestlers performing movements of high coordination complexity during gaming activities will largely depend on the level of physical training of the athletes. However, it is much more important that these adjectives develop much more than the number required to perform specific movement tasks. If the mentioned actions are performed within the athlete’s physical capabilities, that is, without reserve, they significantly lose their effectiveness. A number of studies by specialists in sports games note that physical, and in most cases, speed and strength training, are tasks that conflict with each other.
Keywords: physical training, speed-strength, jumping, wrestlers, technical-tactical.